PERAN KELOMPOK TANI TERHADAP PRODUKTIVITAS JAGUNG DI KECAMATAN GERUNG KABUPATEN LOMBOK BARAT - MADE SUMA WEDASTRA (SOSIAL SAINS DAN TEKNOLOGI, 2022)
This study aims to analyze the role of farmer groups on maize productivity in Gerung District, West Lombok Regency. This research is descriptive research which was conducted in Mesanggok Village, Gapuk and Suka Makmur Village, Gerung District, West Lombok Regency, using a proportional sampling based on the widest corn crop area, using a sample of 78 farmers, determined by proportional random sampling.The data uses a score based on the Likert scale, then analyzed using Chi- Square (X2) analysis. From the results of the study, it can be concluded that statistically the participation of farmers in farmer group members has a role in corn productivity, but is not significant. This is indicated by the results of X2 Count (1.94) < X2 table (9.49), the participation of farmers in farmer group members does not play a significant role in productivity due to internal factors, namely the ownership of farming capital which is still lacking, so that the purchase of production facilities such as fertilizers which is lacking and has an impact on corn production that is not optimal and also due to external factors such as uncertain natural factors, such as rain falling on the flowering process as a result many corn plant flowers fall out.